2013
DOI: 10.1086/671263
|View full text |Cite
|
Sign up to set email alerts
|

Admission Surveillance for Carbapenamase-Producing Enterobacteriaceae at a Long-Term Acute Care Hospital

Abstract: Carbapenemase-producing Enterobacteriaceae (CPE) are of increasing prevalence worldwide, and long-term acute care hospitals (LTACHs) have been implicated in several outbreaks in the United States. This prospective study of routine screening for CPE on admission to a LTACH demonstrates a high prevalence of CPE colonization in central Virginia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 11 publications
0
24
0
Order By: Relevance
“…Isolates were prospectively collected from August 2007 to December 2012 through the Clinical Microbiology Laboratory of the University of Virginia Health System, which serves a 619-bed tertiary care hospital, outpatient clinics in central Virginia, and since August 2010, a 40-bed long-term acute care hospital. From April 2009, weekly surveillance by perirectal swab was performed in all inpatient units with historically high transmission or where there was a patient who was known to be colonized or infected with carbapenemase-producing Enterobacteriaceae (CPE) by previously described methods ( 40 , 42 , 43 ). Enterobacteriaceae isolates from nonsurveillance clinical samples that were flagged as possible extended-spectrum β-lactamase (ESBL) producing or had an ertapenem MIC of ≥1 μg/ml by automated susceptibility profiling (VITEK2; bioMérieux, Durham, NC) underwent carbapenemase phenotypic testing by the modified Hodge test (August 2007 to June 2008) or the indirect carbapenemase test (July 2008 to December 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Isolates were prospectively collected from August 2007 to December 2012 through the Clinical Microbiology Laboratory of the University of Virginia Health System, which serves a 619-bed tertiary care hospital, outpatient clinics in central Virginia, and since August 2010, a 40-bed long-term acute care hospital. From April 2009, weekly surveillance by perirectal swab was performed in all inpatient units with historically high transmission or where there was a patient who was known to be colonized or infected with carbapenemase-producing Enterobacteriaceae (CPE) by previously described methods ( 40 , 42 , 43 ). Enterobacteriaceae isolates from nonsurveillance clinical samples that were flagged as possible extended-spectrum β-lactamase (ESBL) producing or had an ertapenem MIC of ≥1 μg/ml by automated susceptibility profiling (VITEK2; bioMérieux, Durham, NC) underwent carbapenemase phenotypic testing by the modified Hodge test (August 2007 to June 2008) or the indirect carbapenemase test (July 2008 to December 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Isolates were prospectively collected from August 2007 to September 2012 through the Clinical Microbiology Laboratory of the University of Virginia Health System (UVaHS), which serves a 619-bed tertiary care hospital, outpatient clinics in central Virginia, and since August 2010, a 40-bed long-term acute care hospital (LTACH). Weekly surveillance by perirectal swab was performed on all inpatients in units where there was a patient who was known to be colonized or infected with carbapenemase-producing Enterobacteriaceae (CPE), as previously described ( 32 34 ). Enterobacteriaceae from nonsurveillance clinical samples that were flagged as possibly producing an extended-spectrum β-lactamase (ESBL) or that had an ertapenem MIC of ≥1 μg/ml by automated susceptibility profiling (Vitek 2; bioMérieux, Durham, NC) underwent carbapenemase phenotypic testing using the modified Hodge test (August 2007 to June 2008) or the indirect carbapenemase test (July 2008 to September 2012) ( 35 ).…”
Section: Methodsmentioning
confidence: 99%
“…Despite the risk of CRE in long-term care facilities, some studies have reported very low prevalence of CRE at such facilitates and this could be due to several factors such as active surveillance and poor detection methods [ 64 ]. A prospective study in Central Virginia by Lewis et al [ 65 ] concluded that CRE is more prevalent in regional acute care institutions than Long-term acute care hospitals (LTACHs) [ 65 ].…”
Section: Development Of Carbapenem Resistancementioning
confidence: 99%